Developing Risk Prediction Models for Kidney Injury and Assessing Incremental Value for Novel Biomarkers - Kerr, Kathleen F. (American Society of Nephrology, 2014)
The field of nephrology is actively involved in developing biomarkers and improving models for predicting patients’ risks of AKI and CKD and their outcomes. However, some important aspects of evaluating biomarkers and risk models are not widely appreciated, and statistical methods are still evolving. This review describes some of the most important statistical concepts for this area of research and identifies common pitfalls. Particular attention is paid to metrics proposed within the last 5 years for quantifying the incremental predictive value of a new biomarker.